A Retrospective View on the First Three Years of China (Shanghai) Pilot Free Trade Zone. Issue 4 (4th July 2017) - Hu, Jiaxiang
Abstract : As a test ground for new policies, the China (Shanghai) Pilot Free Trade Zone (SPFTZ) has been authorized for three years by the Chinese top legislature to suspend the application of certain provisions of the three foreign investment laws. Different from all the previous SEZs which have received some incentive policies from the central government, the SPFTZ has not been offered any preferential treatment. Instead, it has been encouraged to experiment with new innovative measures in administration. During the first three years of piloting reforms, the SPFTZ shall expedite the functional transformation of the government through limiting the administrative power; expand the opening up of service sectors by releasing the limitations on market access; streamline the administrative regulation on foreign investment; develop the multinational corporation headquarter economy with more sophisticated facilities, and try to experiment with new trade forms. As such, experience hence gained shall serve nationwide with new ideas and approaches in the next round of economic reforms.